Impact of Circadian Meal Timing on Cardiovascular Health: A Comprehensive Review - Fatima, Ghizal; Dhalla, Naranjan S; Khan, Sadaf (Scripta Medica, 2025)
Cardiovascular health is influenced not only by the quality of diet but also by the timing of meals. Circadian rhythms, the body’s internal biological clock, regulate physiological processes, including metabolism, hormone secretion and cardiovascular function. Disruptions in these rhythms, such as irregular meal timing, have been linked to an increased risk of cardiovascular diseases (CVD). There is a strong association between delayed meal timing, particularly late-night eating and breakfast skipping and heightened cardiovascular and cerebrovascular risks. A large-scale European study has suggested that prolonged overnight fasting may lower the risk of CVD and stroke. Emerging dietary approaches, such as time-restricted eating (TRE) and chrono-nutrition, have gained attention for their potential in mitigating metabolic disorders and promoting cardiovascular health. This review explores the intricate relationship between circadian-regulated meal timing and cardiovascular outcomes, analysing molecular mechanisms, clinical evidence and possible dietary interventions. By understanding the role of chrono-nutrition, this review aims to provide insights into optimising meal schedules to enhance cardiovascular well-being and reduce disease risk. In addition to melatonin’s endogenous regulation, dietary sources of melatonin and chronobiotic nutrients (eg, walnuts, tart cherries, oats) may help support circadian alignment. Strategic intake of these foods, especially during evening hours, could enhance melatonin levels and improve cardiovascular outcomes. Moreover, the timing of other compounds like caffeine has emerged as a modifiable factor, with studies showing that morning coffee consumption may reduce cardiovascular and cancer mortality. While intermittent fasting and caloric restriction both reduce caloric intake, these operate through distinct mechanisms. Caloric restriction focuses on reducing total energy consumption, whereas meal timing strategies emphasise aligning food intake with circadian rhythms without necessarily altering caloric quantity. This distinction is critical, as it supports the view on circadian physiology in metabolic regulation.